2011
DOI: 10.1242/dev.063354
|View full text |Cite
|
Sign up to set email alerts
|

Polarity mediates asymmetric trafficking of the Gβ heterotrimeric G-protein subunit GPB-1 inC. elegansembryos

Abstract: SUMMARYAsymmetric cell division is an evolutionarily conserved process that gives rise to daughter cells with different fates. In one-cell stage C. elegans embryos, this process is accompanied by asymmetric spindle positioning, which is regulated by anterior-posterior (A-P) polarity cues and driven by force generators located at the cell membrane. These force generators comprise two G proteins, the coiled-coil protein LIN-5 and the GoLoco protein GPR-1/2. The distribution of GPR-1/2 at the cell membrane is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
0
33
2
Order By: Relevance
“…In C. elegans, GaÁGDP levels are also modulated by Gbg, since depletion of Gbg results in excess pulling forces, presumably because excess GaÁGDP is available for interaction with GPR-1/2 [44,46]. Intriguingly, intracellular trafficking of the Gb protein GPB-1 is modulated in time and space in C. elegans embryos in a manner consistent with it dictating cortical GPR-1/2 localization [47]. This raises the possibility that intracellular trafficking is crucial for proper spindle positioning, as is the case for other aspects of asymmetric cell division, for instance in Drosophila sensory organ precursor cells [48,49].…”
Section: Cortical Dynein: a Force-generating Motormentioning
confidence: 98%
“…In C. elegans, GaÁGDP levels are also modulated by Gbg, since depletion of Gbg results in excess pulling forces, presumably because excess GaÁGDP is available for interaction with GPR-1/2 [44,46]. Intriguingly, intracellular trafficking of the Gb protein GPB-1 is modulated in time and space in C. elegans embryos in a manner consistent with it dictating cortical GPR-1/2 localization [47]. This raises the possibility that intracellular trafficking is crucial for proper spindle positioning, as is the case for other aspects of asymmetric cell division, for instance in Drosophila sensory organ precursor cells [48,49].…”
Section: Cortical Dynein: a Force-generating Motormentioning
confidence: 98%
“…First, endocytosis in general affects the actin cytoskeleton and reciprocally, making it challenging to analyze the two processes separately (reviewed by Galletta and Cooper, 2009). Second, inhibiting endocytosis in one-cell C. elegans embryos using a dynamin mutant results in lower levels of cortical GPB-1, thus probably influencing force generation via increased cortical dynein (Thyagarajan et al, 2011). This could explain the clathrin-like centration/rotation phenotype observed upon depletion of the early endosomal protein RAB-5 (Hyenne et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Primary mouse antibodies against α-tubulin (1/300; DM1A, Sigma), GFP (1/100; MAB3580, Millipore) were used together with rabbit antibodies against GPB-1 (1/200; Thyagarajan et al, 2011), LIN-5 (1/300;Nguyen-Ngoc et al, 2007), DHC-1 (1/100; Kotak et al, 2012), PGL-1 (1/300; Kawasaki et al, 1998) or TAC-1 (1/500; Bellanger and Gönczy, 2003). Secondary antibodies were Alexa488-conjugated goat anti-mouse (1:500; Life Technologies, A11001) and Cy3-conjugated goat anti-rabbit (1/1000; Jackson ImmunoResearch, 711-165-152).…”
Section: Antibodies Western Blotting and Indirect Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the asymmetry in Gβγ could contribute to the asymmetry in pulling forces and posterior displacement of the spindle in mitosis. A recent study showed dynamic regulation of cortical GPB-1 levels and trafficking through both early endosomes and recycling endosomes (Thyagarajan et al 2011). In metaphase of the zygote, trafficking rates are higher in the anterior than the posterior, and more GPB-1 remains present in endosomal vesicles in the posterior.…”
Section: The Gα Gtpase Cycle Is Essential For Pulling Force Generationmentioning
confidence: 99%